PERBANDINGAN EFEK KOMBINASI MANUVER EPLEY DAN BRANDTDAROFF DENGAN MANUVER EPLEY TERHADAP PERBAIKAN DERAJAT KLINIS BENIGN PAROXYSMAL POSITIONAL VERTIGO BPPV - Meryana*, A. Kurnia Bintang**, Muh. Akbar**, Susi Aulina**, Yudy Goysal**, Arifin Limoa*** (Neurona Majalah Kedokteran Neuro Sains, 2011)
INTRODUCTION BENIGN PAROXYSMAL POSITIONAL VERTIGO BPPV IS THE COMMONEST CAUSE O VERTIGO CASES THE MAIN THERAPY OF BPPV IS OTOLITH REPOSITION WITH EPLEY MANEUVER BRANDTDAROFF MANEUVER ALSO CAN BE PERFORMED AS CENTRAL HABITUATION EXERCISE